The Implementation of Hypnoteaching Methods to Improve Good Learning Attitude in Thematic Learning - Hikmah, Shofiatul; Lessy, Zulkipli (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
This research was initiated by the problem of learning attitudes in class IV MIN 1 Bantul students, which were not conducive. This caused the delivery of thematic material not entirely accepted because many students still talk to themselves, play alone, and often even have permission to go to the bathroom. The research aimed to determine the improvement of learning attitudes that were initially not conducive to good learning attitudes using the hypnoteaching method. This study used a qualitative method. Researchers use data from various sources, such as interviews, questionnaires, and documentation. This research was carried out on class IV students of MIN 1 Bantul. The implementation of hypnoteaching that teachers carried out was using positive suggestion sentences spoken by the teacher and followed by students as in the following example sentences: